Policy As a Field of Management Theory - Mintzberg, Henry (Academy of Management Review, 1977)
A conflict exists between rigor and relevance in relation to the role of Management Policy in the management school. The concepts of Management Policy, being crucially important to contemporary organizations, must be given attention by teachers and researchers. To be relevant, policy research must be softer and encompass a richer array of variables than in other fields of management. Management Policy should be taught from the perspective of descriptive theory. Five topic areas are reviewed to indicate that sufficient empirical research exists to enable this to be done.